(untitled) (Global Journal of Computer Science and Technology, 2023)
As the demand for real-time secure and scalable transactions continues to rise the intersection of 5G mobile connectivity and blockchain technology presents a promising solution This paper proposes a novel approach to leverage the high-speed and low-latency capabilities of 5G mobile networks integrating them as nodes in a Layer 1 Proof of Authority PoA blockchain architecture for microtransactions Several advantages are achieved by utilising 5G mobile connections as nodes in the blockchain network Firstly the ultra-fast data transmission speeds and low network latency of 5G networks enhance the efficiency of blockchain transactions enabling near-instantaneous settlement of microtransactions Secondly the distributed nature of the blockchain combined with the security features provided by 5G networks ensures a robust and tamper-proof transactional environment